Modeling of value flows in logistics networks. Comparison of basic tools - Mazur Karolina; Milewski Radosław (Management)
The article presents the necessity of introducing modern systems for analyzing value flows in modern logistics networks. The essence of logistic networks and requirements for analytical systems have been presented. The main available approaches to analyzing value flows in the network have been identified: e3-value modeling, c3-value modeling framework, Value Network AnalysisTM, SimulValor, Modified SimulValor. These approaches (called models) were subjected to a critical analysis on the basis of which the basic directions of their development were indicated.